An invitation on the study of univalent and multivalent functions - A. W. Goodman (International Journal of Mathematics and Mathematical Sciences)
We begin with the basic definition and some very simple examples from the theory of univalent functions. After a brief look at the literature, we survey the progress that has been made on certain problems in this field. The article ends with a few open questions.